2017
DOI: 10.1590/0103-6440201701050
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastic Fibrosarcoma: A Case Report and Literature Review

Abstract: Here is described a case of ameloblastic fibrosarcoma (AFS) affecting the posterior mandible of a woman who was treated surgically and recovered without signs of recurrence or metastasis after 12 years of follow-up. Tumor sections were immunostained for cell cycle, epithelial and mesenchymal markers. Immunohistochemical analysis evidenced high Ki-67 positivity in stromal cells (mean of 20.9 cells/High power field). Epithelial cells displayed strong positivity for p53, p63 and cytokeratin 19. In addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…31 In addition, the average of Ki-67 immunoexpression of patients with odontogenic carcinosarcoma and ameloblastic fibrosarcoma was 10.1% to 45% and 10% to 20%, respectively. 32,33 In CCOC, studies showed low expression of Ki-67. 34 In contrast, in a Brazilian series of 7 cases, Loyola et al 35 reported that the mean number of Ki-67-positive cells was 35.2 cells/highpower field.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, the average of Ki-67 immunoexpression of patients with odontogenic carcinosarcoma and ameloblastic fibrosarcoma was 10.1% to 45% and 10% to 20%, respectively. 32,33 In CCOC, studies showed low expression of Ki-67. 34 In contrast, in a Brazilian series of 7 cases, Loyola et al 35 reported that the mean number of Ki-67-positive cells was 35.2 cells/highpower field.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 and the p53 tumor suppressor gene were useful to determine proliferation. [ 14 15 16 17 18 24 25 26 27 28 29 30 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Dr. Takuji Tanaka and co-workers first reported OT that was composed of a mixture of malignant ameloblastoma (ameloblastic carcinoma) and fibrosarcoma. [ 6 ] In 1992, WHO Classification of OTs introduced OCS. In 2005, the WHO removed OCS from the OT classification because of unknown origin and difficulty in separating from the spindle-cell ameloblastic carcinoma (SC-AMECA).…”
Section: Introductionmentioning
confidence: 99%
“…There have been few IHC investigations on ameloblastic fibroma. Some researchers evaluated highly aggressive ameloblastic fibromas to rule out malignant transformation and reported the Ki67 marker in the epithelial and mesenchymal components of tumors, as well as P53 in the epithelial component [ 27 ]. Moreover, postnatal mesenchymal stem cells have been found in the dental pulp and some odontogenic tumors such as ameloblastic fibroma, with the ability to proliferate and differentiate, and they are currently considered for disease management and regenerative therapy [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%